Circulating tumor markers: Predictors of incomplete cytoreduction and powerful determinants of outcome in pseudomyxoma peritonei. Issue 1 (29th May 2013) - Kusamura, Shigeki; Hutanu, Ionut; Baratti, Dario; Deraco, Marcello
Abstract Background Incomplete cytoreduction (IC) is one of the main prognostic factor in pseudomyxoma peritonei (PMP). We evaluated the ability of preoperative Ca125, CEA, and Ca19‐9 to predict IC and prognosis in PMP. Methods One hundred fifty‐six cases elected candidate to cytoreductive surgery and hyperthermic intraperitoneal chemotherapy from 1996 to 2011 were included in the study. We assessed the: (1) optimal cut‐off values for circulating Tumor markers (CTM) in predicting IC (residual disease >2.5 mm) using receiver‐operating characteristics (ROC); (2) discriminant power of CTM and risk prediction models for IC by calculating the area under ROC curve (AUC‐ROC); (3) prognostic factors using Cox proportional‐hazard model. Results Optimal cut‐offs were 125 U/ml for Ca125, 18 ng/ml for CEA, and 89 U/ml for Ca19‐9. The AUCs‐ROC were 0.76, 0.68, and 0.69 for Ca125, CEA, and Ca19‐9, respectively. The addition of CTM to risk prediction model that considered preoperative clinicopathological factors increased marginally the AUC‐ROC (0.80–0.84). Ca125 > 125 U/ml, Ca19‐9 > 89 U/ml independently affected overall survival. Conclusions Preoperative CTMs were reasonable but not perfect discriminators of IC. Moreover, Ca125 and Ca19‐9, using new cut‐off values, were proven to be new strong prognostic factors that overcome the value of disease extension and histological subtype. J. Surg. Oncol. 2013;108:1–8. © 2013 Wiley Periodicals, Inc.